60 Cardiac device implantation and complications in the west of Ireland; 6 years and a pandemic later. (6th October 2022) - Campbell, R; Birrane, J; Smyth, Y; MacNeill, B; Crowley, J; Nash, P; Hynes, B
Abstract : Introduction: The rate of cardiac device insertion continues to rise worldwide, largely due to an aging population but also from technical advances. While these devices confer a clinical benefit, they are also associated with many complications that can cause significant morbidity and financial burden. Our aim was to re-look at rates of implanted cardiac devices in our centre and compare it to a previous 2014 study and the most recent ESC quality indicators for the care and outcomes of cardiac pacing. Methods: We collected data retrospectively on cardiac device implantation from January to June 2020 in Galway. Patients were identified via device database and complications were recorded as per discharge summaries and documentation available on Evolve IT system. Results: 164 patients underwent cardiac device implantation from January to June 2020 with 37 (22.6%) of these performed in a private hospital owing to Covid restrictions on activity in UHG. 115 (70.1%) were male; with a mean age of 72.4 (± 13.4 years), similar to previous study (mean 74.8). The most common procedure was pacemaker insertion; 85 (51.8%) with the majority being dual chamber at 56 (65.8%), reduced from 2014 at which time pacemakers accounted for 85% of procedures. The most common indication for a pacemaker was symptomatic bradyarrhythmia or pauses; 50 (30.5%). Temporary pacing was required in 12 patients (7.3%). ICD accounted for 36 (22%), with 22 (61%) for primary prevention and 14 (38.9%) for secondary prevention. 4 patients had a CRT device inserted with all of them being an upgrade from an existing device. Routine change of generator for end of life accounted for 35 procedures (21.3%). Our patient population had an average of 4.6 comorbidities (SD 2.3), with hypertension, coronary artery disease and atrial fibrillation being the most common. In line with ESC recommendations, most patients (83.5%) received prophylactic antibiotics 1hr pre incision, commonly Flucloxacillin. 15 patients (9.1%) experienced a complication (average age 72 years), including: lead dislodgement 2 (1.2), pneumothorax 3 (1.8%), hematoma 4 (2.4%), pericardial effusion 1 (0.6%), ventricular perforation 1 (0.6%) and replant revision 3 (1.8%). Of the 4 hematoma patients, 1 was on NOAC, 1 therapeutic Enoxaparin and 2 were taking Aspirin monotherapy. Among the 3 patients who experienced an infection, 2 had hypertension, hyperlipidaemia, diabetes and heart failure. Finally, 94 (57%) received the recommended device check within 2–12 weeks of insertion with a mean waiting time of 70 days (IQR 53.5 – 113.5). Conclusion: Despite the pandemic, UHG has managed to find alternative solutions to ensure an ongoing high volume of device insertions with a relatively low rate of complications in an at-risk aging population. Potential areas for quality improvement in the future could include: changes to the admission proforma to make important information easier to collect and more timely follow-up post-implantation.